FACTORS WHICH INFLUENTIAL TO CONVERSION BTA AND CULTURE IN MULTI-DRUG RESISTANCE TUBERCULOSIS PATIENTS AT H. ADAM MALIK GENERAL HOSPITAL MEDAN YEAR 2020- 2021: English - Mayer Remora Situmorang; Noni Soeroso (Jurnal Endurance, 2023)
Conversion of BTA test and culture is an indicator of monitoring MDR TB treatment where the state of Mycobacterium tuberculosis simultaneously shows negative results on BTA examination and culture. This study aims to determine the factors that influence BTA conversion and culture in MDR TB patients at H. Adam Malik Hospital Medan in 2020 - 2021. This descriptive observational study was conducted with across sectional design. The population is all MDR TB patients recorded at the MDR TB Poly of H.Adam Malik Hospital who started treatment from 2020 – 2021 as many as 104 people. The number of samples was 50 people. Univariate and bivariate data analysis using chi-square statistical test, with 95% confidence level (α=0.05).The results of the bivariate analysis showed that the variables of medication adherence (p = 0.007) (p = 0.001), drug side effects (p = 0.047) (p = 0.008), drug ingestion supervisors (p = 0.001) (p = 0.028), and distance to health care (p = 0.025) (p = 0.047) together had a significant effect on BTA conversion and culture of MDR TB patients.It is expected that health care providers will improve services in health facilities, increase access to MDR TB treatment, and conduct counseling on handling drug side effects. To MDR TB patients to regularly carry out treatment, consult if there are side effects, and control regularly until treatment is complete. For the entire community to implement a clean and healthy lifestyle (PHBS).